Vehicle clamping and alternative parking management and control systems - Mohammed, Mokhaled Mustafa; Khan, Imran Moez; Khalifa, Othman Omran (2011)
Vehicle clamping is a practice that started in the 1950’s in order to enforce traffic and parking regulations usually inside private premises.It often involves the immobilization of a vehicle via a wheel lock that is attached to the tyres of a car in order to make sure that it cannot be driven. However, not only is this practice burdensome to drivers, there are also serious ethical issues surrounding it that has even made it illegal in certain countries. Several of these ethical problems are mentioned, and an Islamic ethical perspective is provided on vehicle clamping as a justification for discarding the practice completely. It is acknowledged that an alternative system to regulate the parking area according to laws and preventing chaos is crucial for all public parking areas. There are numerous systems which would provide simple, effective, and efficient alternatives to clamping. In this paper we would review and describe two different system configurations to replace vehicle clamping. The first system configuration utilizes passive RFIDs, the second technique uses a camera system to extract the vehicle license plate number, as alternatives to vehicle clamping. A traffic simulation is conducted using Arena process simulator with data collected at the IIUM Gombak campus to evaluate the effects of deploying these systems on the traffic flow of vehicles inside such a campus.